2015
DOI: 10.4236/ajps.2015.69151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clammy Inula (<i>Inula viscose</i>) Plant Extract in Combination with a Low Dose of the Fungicide Iprodione on <i>Botrytis cinerea in Vitro</i> and <i>in Vivo</i>

Abstract: The effect of native medical plant "Clammy Inula" (Inula viscosa L.) in combination with a low dose of the fungicide iprodione (Rovral ® ) against gray mould disease (Botryis cinerea Pers.) was evaluated in vitro and in vivo. The results revealed that the plant extract had antifungal effect on mycelial growth rate and conidial germiation of pathogen isolates. The plant extract at the concentration of 1% -4% and the fungicide iprodione at the concentration of 0.2 -9 µg•ml −1 significantly reduced the mycelium g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ali-Shtayeh et al [ 45 ] reported that the water extract of D. viscosa was active against C. albicans by disc-diffusion method, while Al-Masri et al [ 46 ] demonstrated antifungal activity against Botryis cinerea in terms of reduction of mycelium growth and germination when the hydrodistillation of D. viscosa was applied in combination with a low dose of the fungicide iprodione. Moreover, a number of studies reported stronger activity of alcohol extracts of D. viscosa , mainly methanol and ethanol, on both fungal and bacterial strains [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali-Shtayeh et al [ 45 ] reported that the water extract of D. viscosa was active against C. albicans by disc-diffusion method, while Al-Masri et al [ 46 ] demonstrated antifungal activity against Botryis cinerea in terms of reduction of mycelium growth and germination when the hydrodistillation of D. viscosa was applied in combination with a low dose of the fungicide iprodione. Moreover, a number of studies reported stronger activity of alcohol extracts of D. viscosa , mainly methanol and ethanol, on both fungal and bacterial strains [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The search for substances of natural origin with antiphytoviral activity is particularly important today to support biological production and the replacement of synthetic chemicals with natural agents. Scientific literature reports that the application of water extracts of D. viscosa in combination with a low dose of the effective fungicide iprodione may be a viable way to reduce the severity of gray mold disease [ 46 ]. A mixture of acetone and n -hexane extract of D. viscosa emulsified in water effectively controlled downy mildew of cucumber, late blight of potato or tomato, powdery mildew of wheat, and rust of sunflower [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study show that Dittrichia viscosa (Inula) had the highest antifungal activity among all the tested plants. Inula plants contain compounds with antiviral, antibacterial, antifungal, nematicidal, and cytotoxic activities, and have a protective effect against oxidative stress and genotoxicity (Al-Masri et al, 2015;Koc et al, 2018). The major classes of phytochemicals present in the tested Inula were alkaloids, glycosides, phenols, tannins, and terpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…D viscosa is a plant known in Mediterranean traditional medicine and agricultural practices (Table 1). Weed management [4,8,54,55] Pest control [40,[56][57][58][59][60] Antifungal control [31,[61][62][63][64] Biomass production [65] Regulating Bioindicator [36,66,67] Bioaccumulator [36,[68][69][70][71] Phytoremediation [36,43,55,72,73] Desertification control [33,42,74]…”
Section: Dittrichia Viscosa Ecosystem Servicesmentioning
confidence: 99%